Effect of neutron irradiation on Nb3Sn wire. (10th January 2019) - Nishimura, Arata; Nakamoto, Tateshi; Yoshida, Makoto; Iio, Masami; Yamazaki, Masanori; Toyama, Takeshi; Hishinuma, Yoshimitsu; Oguro, Hidetoshi; Awaji, Satoru
Abstract: A Nb3 Sn wire which was manufactured for the ITER toroidal field coil conductor by a bronze route process was prepared for this study to investigate the effect of neutron irradiation on the critical current in a high magnetic field. The critical current of the virgin wire was measured in liquid helium with a 28 T hybrid superconducting magnet at the High Field Laboratory for Superconducting Materials in Tohoku University. It was also measured in vacuum with a heat conduction type variable temperature insert (VTI) at the International Research Center for Nuclear Materials Science at Tohoku University. The wire was irradiated at below 100 °C by fission neutrons at up to 4.9 × 10 22 neutrons m −2 (>0.1 MeV) at BR2 in Belgium, and the critical current after the irradiation was evaluated with a VTI in the range of 8–15.5 T. The difference of the critical current measured with two facilities was discussed, focussing on Joule heating of the sample holder which was made of pure copper, and the neutron irradiation effect on the critical current was investigated in the range of up to 15.5 T. The results show that the critical current measured in vacuum becomes lower than that in liquid helium because of the temperature rise of the sample holder where the sample was soldered, the critical current was increased by the neutron irradiation, and the current ratio (IC /IC0 ) was almost constant of 1.75 in the range of 8–15.5 T at around 4 K.